An investigation of the dynamic characteristics of cracked beam / Ahmad Azlan Mat lsa and Shahril Kushairi - Mat lsa, Ahmad Azlan; Kushairi, Shahril (2006)
Structural defects have an adversely effect on its service life. It alters the dynamic characteristics. The change is characterized by changes in the eigenparameters, i.e. natural frequency, damping values and mode shapes associated with each natural frequency. Thus, defect detection even at the initiation stage is an important consideration to guarantee the component safety and prolong the life service of the structure and hence safe costs from catastrophic failure. The main objective of the project is to obtain information about the variation of the dynamic properties with the location and depth of cracks in beam Analytical, numerical and experimental analysis was carried out to compared the cracked beam and uncracked beam dynamic characteristics by using different boundaries conditions, it is shown that the changes in the dynamic characteristics was significant. This information can be used to obtain the amount of damage in structure.